2005
DOI: 10.1111/j.1439-0396.2005.00582.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of selenium inStaphylococcus aureusinhibition in cow's whey

Abstract: Previous investigations have shown that selenium supplementation inhibits growth of mastitis pathogens in cow's milk. The present study was performed to clarify the role of selenium in defence mechanisms of mammary gland. We have examined the effects of selenium supplementation on Staphylococcus aureus growth inhibiting activity in whey. Six selenium-supplemented and six non-supplemented Estonian dairy cows were used for this study. Selenium-supplemented cows received 4 mg organic selenium in the form of selen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Our findings are in agreement with several authors who demonstrated that neutrophils from cows with supplemental Se (inorganic) increased intracellular kill of bacteria, enhanced viability and reduced extracellular hydrogen peroxide concentration as compared to non supplemented cows (Gyang et al, 1984;Grasso et al, 1990;Hogan et al, 1990). Malbe et al (2006) also demonstrated possible involvement of organic Se supplementation (4 mg/day) with Staphylococcus aureus inhibition in cow's whey. In our study, these effects were more pronounced with organic Se at both levels of supplementation.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in agreement with several authors who demonstrated that neutrophils from cows with supplemental Se (inorganic) increased intracellular kill of bacteria, enhanced viability and reduced extracellular hydrogen peroxide concentration as compared to non supplemented cows (Gyang et al, 1984;Grasso et al, 1990;Hogan et al, 1990). Malbe et al (2006) also demonstrated possible involvement of organic Se supplementation (4 mg/day) with Staphylococcus aureus inhibition in cow's whey. In our study, these effects were more pronounced with organic Se at both levels of supplementation.…”
Section: Discussionsupporting
confidence: 93%
“…This fact may be linked to the inhibitory effects of this mineral on staphylococci growth, as previously demonstrated by in vitro studies with S. aureus and Se nanoparticles [ 66 ]. Additionally, it has been observed that supplementation of dairy cattle with Se inhibits the growth of S. aureus in bovine milk, in comparison with control cows [ 67 ]. Similarly, a recent in vivo study has demonstrated that organic Se ameliorates S. aureus induced mastitis in rats [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sodium selenite SCC; GSH-Px d SCC decreased significantly (P <0.05) from 2961•10 3 to 630• 10 3 in buffaloes screened positive for intra mammary infections, whereas GSH-Px activity increased significantly. Malbe et al (2006) C 4 mg day À1 in diet (8 weeks)…”
Section: Resultsmentioning
confidence: 99%
“…In an experiment described by Hemingway (1999), 14 of 36 cows receiving intramammary antibiotic infusions at drying off needed extra treatment in the subsequent lactation, whereas only 5 of 36 cows which received additionally 4 mg Se at drying off needed such treatment. Udder health benefits have been attributed to antibacterial activities against S. aureus in milk whey protein (Ali-Vehmas et al , 1997; Malbe et al , 2006). The underlying mechanism of this antibacterial activity is not well understood.…”
Section: Mastitis Susceptibility and Se Statusmentioning
confidence: 99%
See 1 more Smart Citation